Revitalization Of Islamic Moral Education In Strengthening The Religious Character Of Elementary School Children In The Digital Age - Resmiati Resmiati; Septiani Aryanti; Ai Meti Suryani; Try Riduwan Santoso (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Islamic moral education plays a strategic role in shaping the religious character of elementary school students amid the rapid development of the digital age. The main challenges in elementary education today lie not only in cognitive aspects but also in the erosion of moral values, digital ethics, and the lack of religious guidance for children in their use of technology. This study aims to analyze the revitalization of Islamic moral education in strengthening the religious character of elementary school students in the digital age, with a focus on school policies, religious practices, and collaboration between schools and parents. The study employs a qualitative approach using a descriptive field study design. The research location is SDN 3 Kalapasawit in Lakbok Subdistrict, Ciamis Regency, which was selected for its consistent efforts to foster a religious culture and address the digital challenges faced by students. The research subjects included school principals, teachers, school committees, and parents. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis utilized an interactive model that included data reduction, data presentation, and drawing conclusions. The research findings indicate that the revitalization of Islamic moral education is implemented through systematic school policies, consistent religious practices, and active collaboration between schools and families. Religious practices have been shown to foster students’ discipline, responsibility, politeness, and awareness of religious duties, as well as contribute to the regulation of digital behavior. Synergy between schools and parents reinforces the continuity of religious values between the school and home environments. This study confirms that Islamic moral education, when managed in an integrated and collaborative manner, serves as a crucial foundation for shaping the religious character of students who are adaptable and responsible in the digital age.